Anthropology of Islamic Education as A Socio-Cultural-Religious Modernization Strategy in Alam Al-Kudus Islamic Boarding School - Firmansyah, Eka; Tobroni, Tobroni; Romelah, Romelah (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
Study this aim to examine the educational process carried out in pesantren the realm of the Holy. Where is the boarding school? They must use Islamic anthropology education because of the participant base students' condition. Is a community still ethnic with their ethnicity and culture? So that needs the way it doesn't standard so you can educate them. Study This uses paradigm interpretive with a qualitative approach and uses type study ethnography. Research results found that the Modernization process socio-cultural-religious through the Anthropology of Islamic Education is carried out by (1) Using Language Kaili as Language in the primary learning process, (2) teaching materials in Islamic education, (3) giving examples of morals noble (4) teaches life peace and value unity (5) internalize teachings Islam in activity culture (6) Strengthen values monotheism. Whereas the implication namely (1) Easy learning understood, (2) knowing Islam closer, (3) behaving well and politely, (4) guarding unity and harmony (5) distancing self from superstition, heresy, and superstition.